OPTIMASI DESAIN STENT PLA MENGGUNAKAN METODE RESPONSE SURFACE (RSM) UNTUK MEMPEROLAH FLEKSIBILITAS TERBAIK - Sukiman B (Universitas Gadjah Mada, 2018)
The stent installation is one of cardiovascular disease treatments which is selected the most to handle patients with blood vessel disease. As the demand for stents increases, more researches are aimed at developing them. This study aims to obtain the optimal link design to produce the best flexibility to the change of stent angle with minimum stress so as not to injure blood vessel plaque. In this study, the stents are polymer stent with different types of links made with PLA materials with strut mirror (S><) design. The study was conducted on two stent configurations, namely crimped and expanded to determine the ability of angular change and maximum stress experienced by both when bending moment applied. The bending moment test was done through simulation based on finite element method in software Abaqus 6.14. The simulation results were then used as a model-making reference to determine the desired optimization design using the help of Minitab 18 software based on the response surface method. The results of this study indicate that the best optimal flexibility on crimped stent L1 to L5, which is the highest flexibility with von mises stress in the safety limit can be obtained based on a combination of link design parameters in the form of bending moment of 0.0074 N.mm with a thickness of 100 μm L3, and 0,0087 N.mm with a thickness of 106 μm L5. While at the expanded stent L1 to L5, the optimal link design parameter value for obtaining the best flexibility with von mises stress within the safety limit is a bending moment of 0.0075 N.mm with a thickness of 63.78 μm L3, 0.0067 N.mm with a thickness of 70 μm L5.